Russia Re-Emerging Great Power - Kanet, R.; Kanet, R. (Studies in Central and Eastern Europe, 2007)
The authors argue that Vladimir Putin and his advisors are committed to re-establishing Russia as a great power and that the existence of nuclear weapons and the revival of the Russian economy have provided the foundations for an expanded Russian role in global affairs.